Кінетика індукованого лазером теплового випромінювання поруватих вуглецевих матеріалів: залежність від довжини хвилі лазера - Zelensky, S.E.; Kolesnik, O.S.; Yashchuk, V.P. (Publishing house "Academperiodika", 2024)
For the porous carbon material excited by the first and second harmonics of a neodymium laser, the shape of pulsed signals of laser-induced thermal emission is investigated. It is found that the duration of thermal emission pulses significantly depends on the wavelength of the laser excitation, which is caused by the differences in the depth of penetration of laser radiation into the surface layer. The mentioned effect is actual, if the penetration depth of laser radiation exceeds the length of thermal diffusion in the studied material for a time of the order of the laser pulse duration. The computer modeling is carried out for the processes of pulsed laser heating and formation of thermal emission signal. The simulation results showed satisfactory agreement with the measurement results.